Discovering EFL Graduate Students’ Difficulties And Strategies During Self-Directed Web-Based Listening Activities - Muslim, Muhamad Aziz; Sulistyaningrum, Siti Drivoka (CV. Inara, 2024)
This research was conducted to discover the difficulties faced and the strategies employed by students of the Master of English Language Education Study Program during self-directed web-based listening activities at the B2, C1, and C2 levels of CEFR. In this research, the researcher involved 8 students of the Master of English Language Education Study Program at a state university in Indonesia who enrolled in the same class for the English Proficiency for Teachers course. During the course, the students autonomously developed their listening proficiency. At the same time, the students were asked to report their results of listening activities while also identifying and reporting the difficulties they faced and the strategies to overcome the difficulties during the listening activities in the form of task reports and self-reflective writing. The researcher employed the content analysis method to explore the reflective writing and reports written by the students of the Master of English Language Education Study Program to discover the difficulties they faced and the listening strategies they employed. The students’ reflections were analyzed to set the rubric for discovering their difficulties and strategies. Then, the researcher used the rubric as an instrument to analyze the data. As a result, this research has confirmed that students of the Master of English Language Education Study Program faced various difficulties and employed various strategies during the self-directed web-based listening activities at the B2, C1, and C2 levels of CEFR. This research also provides valuable insight for anyone in the English language education field.